Объяснение:
А
х - у = 7
х + у = 11
2х = 18
х + у = 11
1)
2х = 18
х = 18 : 2
х = 9
2)
х + у = 11
9 + у = 11
у = 11 - 9
у = 2
ответ: (9; 2)
Б
2х + у = 3 | * -5
3х + 5у = 8
-10х - 5у = -15
3х + 5у = 8
-7х = -7
3х + 5у = 8
1)
-7х = -7
х = -7 : (-7)
х = 1
2)
3х + 5у = 8
3 * 1 + 5у = 8
3 + 5у = 8
5у = 8 - 3
5у = 5
у = 5 : 5
у = 1
ответ: (1; 1)
В
х = -8
4х - 8у = -27
4х - 8у = -27
4 * (-8) - 8у = -27
-32 - 8у = -27
8у = -32 - (-27)
8у = -32 + 27
8у = -5
у = -5 : 8
у = -0,625
ответ: (-8; -0,625)
Г
7х + 7у = -7
10х + 2у = -5,2 | * -3,5
7х + 7у = -7
-35х - 7у = 18,2
-28х = 11,2
7х + 7у = -7
1)
-28х = 11,2
х = 11,2 : (-28)
х = -0,4
2)
7х + 7у = -7
7 * (-0,4) + 7у = -7
-2,8 + 7у = -7
7у = -7 - (-2,8)
7у = -7 + 2,8
7у = -4,2
у = -4,2 : 7
у = -0,6
ответ: (-0,4; -0,6)
Объяснение:
А
х + 5у = 6 | * -2
2х - 3у = 5
-2х - 10у = -12
2х - 3у = 5
-13у = -7
2х - 3у = 5
1)
-13у = -7
у = -7 : (-13)
у = 7/13
2)
2х - 3у = 5
2х - 3*7/13 = 5
2х - 21/13 = 5
2х = 5 + 21/13
2х = 5 + 1. 8/13
2х = 6. 8/13
2х = 86/13
х = 86/13 : 2
х = 86/13 * 1/2
х = 86/26
х = 43/13
ответ: (43/13; 7/13)
Б
х + у = 18
х - у = 12
2х = 30
х + у = 18
1)
2х = 30
х = 30 : 2
х = 15
2)
х + у = 18
15 + у = 18
у = 18 - 15
у = 3
ответ: (15; 3)
В
2х + 5у = 11
у = -3
2х + 5у = 11
2х + 5 * (-3) = 11
2х - 15 = 11
2х = 11 + 15
2х = 26
х = 26 : 2
х = 13
ответ: (13; -3)
Г
2х - 2у = -2 | * 5
-10х + 5у = -0,5
10х - 10у = -10
-10х + 5у = -0,5
-5у = -10,5
10х - 10у = -10
1)
-5у = -10,5
у = -10,5 : (-5)
у = 2,1
2)
10х - 10у = -10
10х - 10*2,1 = -10
10х - 21 = -10
10х = -10 + 21
10х = 11
х = 11 : 10
х = 1,1
ответ: (1,1; 2,1)
Объяснение:
(x-1)-(x+3)(x-3) = x-1-(x²-9)=x-1-x²+9 = -x²+x+8